Organic disinfectant using coconut shell liquid smoke in the chicken slaughterhouse wastewater treatment plant - Cortheo Donny Yuslan; Budiyono; Sutaryo (E3S Web of Conferences)
Wastewater treatment in Chicken Slaughterhouse is absolutely necessary because it has a very positive impact on environmental preservation and helps remove pathogenic organisms in wastewater before being discharged into the environment. Currently, wastewater treatment still uses chlorine as a disinfectant. However, chlorine has a bad effect on the environment, the purpose of this research is to use an alternative organic material that functions as a disinfectant as coconut shell liquid smoke. This study also observe the effect of using liquid smoke on the value of biochemical oxygen demand (BOD) and chemical oxygen demand (COD) on the output of wastewater.. This experimental research method uses a chemical method by taking samples of wastewater and adding two different doses of liquid smoke and testing for BOD and COD values. With a dose of 0.5% can reduce the COD value by 35% but increase the BOD value by 234%, and a dose of 1% it increases the BOD value by 195% and increases the COD value by 170%. This will allow for further research with the appropriate dosage to understand its relationship to water quality and its connection to environmental sustainability.